The Revanchist City: Downtown Chicago and the Rhetoric of Redevelopment in Bronzeville (Global Journal of Human-Social Science, 2022)
This paper examines and interprets the contrived cycle of disinvestment and reinvestment in Bronzeville-the original settlement area of Blacks in Chicago. The historical political, economic, and social policy of confinement and segregation in Chicago created a high concentration of public housing in Bronzeville. Data reveals that the disinvestment process in Bronzeville correlates with the concentration of public housing. As the cost of local, state, and federal practices to maintain and concentrate public housing in Bronzeville increased, a new public policy of housing demolition to create mixed income housing development, coupled with decline of Chicago's manufacturing base and subsequent rise in information and consumption-based economy, sparked reinvestment. Our data reveal that the process of disinvestment and reinvestment-gentrification-doesn't just happen by chance but in fact is socially contrived and planned. Under the rhetoric and language of being concerned for the well-being of the urban poor, the primary goal of downtown Chicago and other public and private interests is to reclaim urban space for the creation of a middle and White upper-class elite consumer base in Bronzeville, as well as a space of cultural consumption for tourists.